Specificity of the Organization of Text Space in the Novel of E. Vodolazkin «Soloviev and Larionov» - Fateeva, Natalia (Slavica, 2020)
The article analyzes the specificity of the organization of the text space in the novel, the relationship of its title and main characters is clarified. The main motives of the story that unite the heroes and motivate the interweaving of their destinies are highlighted: the railway, the sea, the horse and the rider, childhood, life and death. It is proved that the text of the novel is built as a search for an answer to the question about the secrets of the life of General Larionov.